Correction of a Splicing Mutation Affecting an Unverricht-Lundborg Disease Patient by Antisense Therapy - Matos, L. (2018)
Unverricht-Lundborg disease (ULD) is a common form of progressive myoclonic epilepsy caused by mutations in the cystatin B gene (CSTB) that encodes an inhibitor of several lysosomal cathepsins. Presently, only pharmacological treatment and psychosocial support are available for ULD patients. To overcome the pathogenic effect of the ULD splicing mutation c.66G>A (exon 1), we investigated whether an antisense oligonucleotide therapeutic strategy could correct the defect in patient cells. A specific locked nucleic acid (LNA) antisense oligonucleotide was designed to block a cryptic 5'ss in intron 1. Overall, this approach allowed the restoration of the normal splicing pattern. Furthermore, the recovery was both sequence and dose-specific. In general, this work provides a proof of principle on the correction of a CSTB gene defect causing ULD through a mutation-specific antisense therapy. It adds evidence to the feasibility of this approach, joining the many studies that are paving the way for translating antisense technology into the clinical practice. The insights detailed herein make mutation-based therapy a clear candidate for personalized treatment of ULD patients, encouraging similar investigations into other genetic diseases.